Long-term funding of community projects has contributed to mitigation of illegal activities within a premier African protected area, Bwindi impenetrable National Park, Uganda - Bitariho, Robert; Akampurira, Emmanuel; Mugerwa, Badru (Conservation Science and Practice, 2022)
At Bwindi Impenetrable National Park (hereafter Bwindi), illegal activities often provide major challenges to park management. In 1994, an Integrated Conservation and Development Program (ICDP) was introduced in Bwindi as a novel park management approach that included among others, funding of community projects in park adjacent communities. This study assessed key drivers of illegal activities and the impact of long-term funding of community projects on illegal activities reduction in Bwindi. We used a 21-year-old illegal activities dataset, environmental drivers' dataset; a 21-year-old dataset of funded community projects and interviews data of 2734 households located around Bwindi for the study. A total of 3383 illegal activities and 338 funded community projects were recorded. Key drivers of illegal activities in Bwindi were accessibility and the number of funded community projects. Parishes with the highest number of community projects experienced fewer illegal activities. The number of illegal activities was negatively correlated with the number of funded community projects. Water and sanitation and household income-generating projects were the most funded. In conclusion, long-term funding of community projects contributed to reduction in illegal activities. A targeted approach of increasing community projects in those parishes that showed high incidences of illegal activities is recommended.
Keywords: Drivers of illegal activities; Funding community projects; Illegal activities in protected area; Integrated conservation and development